Gas production from a silty hydrate reservoir in the South China Sea using hydraulic fracturing: A numerical simulation. Issue 4 (16th May 2019) - Sun, Jiaxin; Ning, Fulong; Liu, Tianle; Liu, Changling; Chen, Qiang; Li, Yanlong; Cao, Xinxin; Mao, Peixiao; Zhang, Ling; Jiang, Guosheng
Abstract: The low permeability of silty hydrate reservoirs in the South China Sea is a critical issue that threatens safe, efficient, and long‐term gas production from these reservoirs. Hydraulic fracturing is a potentially promising stimulation technology for such low‐permeability reservoirs. Here, we assess the gas production potential of a depressurization horizontal well that is assisted by the hydraulic fracturing using numerical simulation according to field data at site SH2 in this area. In addition, the number of horizontal wells drilled is discussed if commercial production is to be performed at this site. The results show that the production potential can be significantly stimulated at the early production stage by adopting hydraulic fracturing in this reservoir due to a better depressurization effect. However, the increase in gas recovery gradually decreases with the continuous dissociation of gas hydrates, and the evolution trend is similar to that in a reservoir without stimulation during later periods of gas production because the dissociation front gradually moves away from the fractures. From the perspective of production potential, using a horizontal well scheme assisted by the hydraulic fracturing technology for gas recovery from a hydrate deposit can sharply reduce the number of operation wells, shorten the drilling operation time, and boost the economic efficiency. The horizontal well scheme may be an effective way to increase the gas yield if the application of quickly deployed horizontal wells and hydraulic fracturing techniques in such hydrate reservoirs greatly increases in the near future. Abstract : The effect of hydraulic fracturing on gas recovery and the needed minimum number of horizontal operation wells are evaluated for gas hydrate reservoirs in Shenhu area of the South China Sea. The horizontal well scheme may be an effective way to increase the gas yield if the horizontal wells and hydraulic fracturing techniques in such hydrate reservoirs are adopted in the near future.